Pengembangan Modul Service Advisor Talk Menggunakan Framework ERP Odoo 10 Pada PT. Tunas Dwipa Matra - Bambang Hermanto; Igit Sabda Ilman; Ardiansyah Ardiansyah; Qurrota Aini Dila Az Zahra (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
PT. Tunas Dwipa Matra is the main dealer of HONDA motorcycles in Lampung which is engaged in the development of a network of sales, maintenance, repair and service of spare parts for HONDA motorcycles. A service advisor is someone who helps customers at a dealership to understand vehicle maintenance or repair options, answering customer questions before being scheduled with a technician. This study aims to help a service advisor to be able to access materials regarding understanding motor maintenance and repair as well as other program information. The method used in this study is an agile method with a scrum framework. Based on the research conducted, a service advisor talk menu is produced that can be used for workshop employees, especially a service advisor. Tests carried out in the study were Alpha Test, Beta Test, and Functional Test. Based on the test results, it can be concluded that the service advisor talk module can make it easier for a service advisor to get material and program information related to technical work.